Faktor Keputusan Pelanggan dalam Pemilihan Hotel Syariah - Siti Yuni Lestari; Agung Guritno (JIEF : Journal of Islamic Economics and Finance, 2022)
The purpose of the study was to determine the effect of service quality, facilities, location, price, and the application of Islamic business ethics on the decision to stay at Syariah Hotel Solo. This research is a quantitative research using primary data. The method of data collection was done through questionnaires distributed to Syariah Hotel Solo customers. The sample used in this study were 100 respondents with purposive sampling technique. The data obtained were processed with SPSS. This analysis uses instrument test, multiple linear regression test, t test, f test, test, and classical assumption test. Based on the results of the T test the quality of service, facilities, and location have no effect on the decision to stay, while the price and the application of Islamic business ethics have a positive and significant effect on the decision to stay. The results of the F test show that the quality of service, facilities, location, price, and the application of Islamic business ethics simultaneously have a significant positive effect on the decision to stay.